Risk of Tics with Psychostimulants for ADHD - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2016)
Investigators at Yale University, New Haven, CT, conducted a meta-analysis to examine the risk of new onset or worsening of tics caused by psychostimulants used in the treatment of children with ADHD.